Development of Hydroponic Application based on Web and Internet of Things for The Community to Monitor pH and Total Dissolved Solids - Barus, Simon Prananta; Dhamma, Yonathan Arya (International Journal of Research in Community Services, 2024)
Construction of the Mortality Table with Gompertz's Law Using the 2019 TMI Reference